Os ogros têm camadas (dialógicas): a corrosão carnavalesca dos elementos prototípicos dos contos de fadas tradicionais fílmicos em Shrek (2001) - Assis, Ana Carolina Lourenço de (2022)
Fairy tales have always been part of the cultural traditions of different peoples. Through oral accounts, these discursive genres were engendered in the formation of generations, with regard to customs, religiosities and behaviors. From then onwards, the unreal, the magical and the irrational, common categories in the archetypal representations of fairy tales, became recurrent conceptions in the creation of stories, whose prohibited, banned or rejected phenomenologies by society came to be considered possible in the wonderful world. In terms of writing, some names stood out by producing or assembling collections of fairy tales for children, some of them being the german brothers Grimm (Snow White and the seven dwarfs); the french Charles Perrault (Sleeping Beauty) and the danish Hans Christian Andersen (The Little Mermaid). With technological advances, these same tales gained new versions through the cinematographic image. The rise of animation cinema, mainly by the Disney industries, contributed to these narratives, which have resisted for millennia, to establish themselves with the characteristics they have today. However, in the film Shrek (2001), by DreamWorks, we are presented with an animated fairy tale in reverse of these oral and cinematographic stories, in which the problem revolves around the corrosion of filmic texts that present in their plots constructions of oral stories and, thus, considered as "traditional". In the plot, we are taken to follow the adventure of the ogre Shrek in search of Princess Fiona, with which he falls in love on the way. It is on this path that existential dilemmas, identity issues, as well as the chronotopic interferences of the road in the subjects are revealed. Thus, to corroborate this discussion, we use the basic precepts that guide the postulates of the Bakhtin Circle, with regard to discursive genres (BAKHTIN, 2016) (focused on filmic fairy tales); the carnival cosmovision and the philosophy of laughter (BAKHTIN, 2010, 2018) as principles of subversion and corrosion, and the concept of chronotope (BAKHTIN, 2018); furthermore, the research is inserted in the mestizo, hybrid, multidisciplinary and radical area of Applied Linguistics and is based on the philosophical theories of Byung-Chul Han (2017a, 2017b, 2019, 2021), as well as in the concept of hypermodernity by Lipovetsky (2004). Regarding the methodology, the construction and collection of data was developed from a qualitative-interpretative perspective and was used the evidential paradigm of Ginzburg (1986) and the dialogical comparison, first thought by Bakhtin (2017) and later elaborated by Manfrim (2017) and Sobral (2017). It's believed that our corpus presents a conception of the hero, the princess and the grotesque body whose deconstruction of idealized images of children's tales present, in the movie's heterodiscourse, representations that differ from those present in fairy tales.